2007
DOI: 10.1002/eat.20466
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behavior in adolescents: Relationship to weight status, weight control behaviors, and body dissatisfaction

Abstract: Objective: Suicide is associated with full syndromal eating disorders, but it is unclear whether subsyndromal eating disorders carry the same risk. This study examined associations between suicidal behaviors and extreme and less extreme weight control behaviors (EWCB and LWCB, such as fasting, vomiting, meal skipping, etc.), body dissatisfaction, and weight status in adolescents.Method: Data on body dissatisfaction, depressive symptoms, suicidal ideation and attempts, and body mass index (BMI) were drawn from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
101
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 23 publications
13
101
1
8
Order By: Relevance
“…Strong associations have been found between suicide ideation and suicide attempts, and extreme dieting behaviours in a large US adolescent sample (Neumark-Sztainer et al, 1998). More recently, extreme weight control behaviours (e.g., diet pills, self-induced vomiting, laxative use) and less extreme EXTREME DIETING BEHAVIOURS 5 weight control behaviours (e.g., fasting, food restriction, smoke more cigarettes) were found to be associated with higher rates of suicidal ideation and suicide attempts in adolescents (Crow et al, 2008). Similarly, weight control behaviours are independently associated with suicidal thoughts and behaviours in adolescents (Kim et al, 2011).…”
Section: Abstract: Extreme Dieting Behaviours; Psychosocial Correlatementioning
confidence: 94%
“…Strong associations have been found between suicide ideation and suicide attempts, and extreme dieting behaviours in a large US adolescent sample (Neumark-Sztainer et al, 1998). More recently, extreme weight control behaviours (e.g., diet pills, self-induced vomiting, laxative use) and less extreme EXTREME DIETING BEHAVIOURS 5 weight control behaviours (e.g., fasting, food restriction, smoke more cigarettes) were found to be associated with higher rates of suicidal ideation and suicide attempts in adolescents (Crow et al, 2008). Similarly, weight control behaviours are independently associated with suicidal thoughts and behaviours in adolescents (Kim et al, 2011).…”
Section: Abstract: Extreme Dieting Behaviours; Psychosocial Correlatementioning
confidence: 94%
“…Though these factors have been demonstrated to be important predictors of suicidal ideation in people with low BMI (Cook et al 2007;Crow et al 2008;Kim and Kim 2009), no assessment was done with regard to these variables in our survey. Fifthly, reliability and validity of the questionnaire used to assess the BWP is yet to be confirmed, though the questionnaire is commonly used and seems to have good face validity.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, several studies have indicated that the association between BMI and suicidal ideation or self-harming behavior can be mediated or confounded by body weight perception (BWP) in adolescents (Brausch and Gutierrez 2009;Crow et al 2008;Kim and Kim 2009;Orbach et al 2001) . In other words there may be no direct association or causal relationship between BMI and suicidal ideation or behavior among this generation.…”
Section: Introductionmentioning
confidence: 99%
“…Community based studies in adolescents found relationships between ED psychopathology and suicidal ideation, and between SIB and suicide attempts (Miotto et al, 2003;Brunner et al, 2007;Crow et al, 2008;Neumark-Sztainer et al, 1998;Rodriguez-Cano et al, 2006). An association between ED psychopathology and suicidality has been reported across various clinical and community based samples of adolescent patients.…”
Section: Relationship Between Eds Sib and Suicidal Behaviourmentioning
confidence: 99%